Associations between Driving Status, Frequency of Transport use after Driving Cessation, and Social Frailty among Middle-Aged and Older Adults - Tatsuya Fukuei; Shoma Akaida; Yoshiaki Taniguchi; Daijo Shiratsuchi; Yuto Kiuchi; Mana Tateishi; Yukari Aishita; Ryota Kuratsu; Hyuma Makizako (Annals of Geriatric Medicine and Research)
Background The use of transport other than cars is a modifiable factor in the association between driving cessation and social frailty. Clarifying this relationship may serve as a new preventive measure against social frailty among current non-drivers. This study examined the potential association of driving status and transport use with social frailty, as well as between the frequency of transport use and social frailty, among current non-drivers. Methods This study included 977 middle-aged and older adults (average age, 65.3±4.8 years). The participants were classified as transport users (more than a few times a week) and transport non-users (less than a few times a month). Based on driving status and transport use, the groups were further classified into current driver, current non-driver/transport user, and current non-driver/transport non-user groups. The relationships between driving status, transport use, and social frailty were examined using multiple logistic regression. Results The current non-driver group and the transport non-user group were significant association with a higher social frailty. The current non-driver/transport user group showed no association with social frailty compared with the current driver group. The odds ratio for the social frailty rate for The current non-driver/transport non-user group was 2.14 (95% confidence interval, 1.25–3.73). Conclusions Participants who neither drive nor take transport showed significant associations with increased social frailty. Compared with current driver/transport use, current non-driver/transport non-use was associated with social frailty.